THE IMPACT OF BRAND, PRODUCT QUALITY, AND PRICE ON THE DECISION TO PURCHASE A SAMSUNG GALAXY S8 SMARTPHONE IN TUNJUNGAN PLAZA, SURABAYA CITY. - Nuzul Purnama Putra; Sugiharto; Achmad Daengs GS; Bambang Karnain; Rina Dewi; Enny Istanti (PT. Mawadaku Sukses Solusindo, 2023)
The current development of telecommunications is driven by consumer needs for more effective communication. From the middle class to the upper class, they want to have fast communication without being disturbed by the communication process. With this development, the telecommunications industry is increasingly competing to provide the best for market satisfaction, so that more and more mobile phone products are turning into smart phone products with different features and qualities. Such market competition conditions require a telecommunications company to create a more effective and efficient strategy to attract consumers. There are many considerations that consumers think about before purchasing goods/services. Some of them are considering the product to be purchased, by adjusting the desires, needs and benefits that will be obtained after purchasing the product, as well as the price that will be spent to get the product by adjusting purchasing ability. The problem in this research is whether there is an influence of brand, product quality and price variables on the decision to purchase the Samsung Galaxy S8 smartphone at Tunjungan Plaza, Surabaya City? The data used in this research is primary data obtained by distributing questionnaires to Samsung customers at Tunjungan Plaza Surabaya. In partial testing, the brand image variable (X1) has a significant influence on purchasing decisions (Y) with a calculated t of 3.646 which is greater than the t table of 1.98609, with a significance level smaller than 0.05. The product quality variable (X2) has a significant influence on purchasing decisions (Y) with a calculated t of 2.829 which is greater than the t table of 1.98609, with a significance level smaller than 0.05. and the price variable (X3) has a significant influence on purchasing decisions (Y) with a calculated t of 2.239 which is greater than a t table of 9.707 which is greater than a t table of 1.98609, with a significance level smaller than 0.05.